Pemberdayaan UMKM Batik melalui Pelatihan Fotografi Digital di Rizqi Batik Mantaran - Akhta Darussalam, Loga; Kiki Astria, Kadek; Damastuti, Riski (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
This research aims to improve the marketing skills of Batik Rizqi Mantaran MSMEs through photography training using smartphones. The main problem faced by Batik Rizqi Mantaran is the challenge of marketing their batik products in the digital world. The natural dyes used in batik production provide ecological added value, but product marketing is still an obstacle. Through hands-on observation and practical training, the batik makers were taught photography and editing techniques using smartphones. The results showed a significant improvement in the batik makers' ability to produce attractive and high-quality visual content, which plays an important role in product promotion on social media. The training not only improved technical skills but also empowered the local economy by utilizing digital technology. Recommendations for follow-up research include further training in advanced marketing techniques, ongoing technical support, and collaboration with digital platforms to improve promotional effectiveness. This study recognizes the limitation of a small sample size, which requires further research for validation of these findings. Overall, the training had a significant positive impact on the skills and marketing of Rizqi Mantaran Batik MSME products.